The effect of synthetic spider venom peptides on Spodoptera litura - Umi Atasshya Md Domyati. (2015)
ABSTRACT Spider venom is a spider poison that kills insects and small preys before consuming them as well as used for self-defense. The spider is under the phylum Arthropoda and the order Aranea. Spider venom from Pardosa sumatrana has been proven as a potential insecticide towards Spodoptera litura. However, its mode of action is still unknown. Spodoptera litura is known as a destructive polyphagous insect pest in agriculture crops such as cabbage, lettuce and tobacco. This project was carried out to investigate the efficiency of synthetic spider venom peptides of P. sumatrana on third instar larvae of S. litura in terms of paralytic effect, larval mortality, body length, body color and symptoms that can be seen. The S. litura larvae were injected at the lateral mid abdomen. The paralytic effect and larval mortality were recorded daily. Based on the data collected, PSV8 caused the highest percentage of larval mortality compared to PSV4 and PSV7. Besides that, the lethal larvae shrunk and decreased in body length. The color of the body also changed to black.